If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z = -1 Solving 3z = -1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Divide each side by '3'. z = -0.3333333333 Simplifying z = -0.3333333333
| 6+r=15 | | -8=x-13 | | 8+t=9 | | -z+19=9z+19 | | 4x+4=31x-4 | | 16-x=12 | | y-14=14 | | 15x+12=5x-4 | | 3e+4=25 | | 2y-2=6(4-2) | | 2m-3=11 | | -6g-4g=100 | | 126-3x=24x+21 | | 12/3=6/2(3)+3 | | 16t^2-34t+18=0 | | 6x+10x=32 | | x-2(1x+10)=12 | | -0.5y+0.2=0.75y-0.2 | | -8-8x=-55-10x | | 16t^2-128+240=0 | | 1.17+x=2x-1.17 | | 49t^3-4t=0 | | 60-5x=4x+21 | | 9(t-4)+3t=4(3t+4)-12 | | 3+6p=13+6 | | 5x-9x=-24 | | 2p-10=-4(6p+5)+8(-10+3p) | | 5-7x=22-14x | | x^2-17x+72.25=-72+72.25 | | -5s+19=(4+5) | | -9(3x+7)=-8(x-4) | | 92-9=8a |